On Financial Development and Economic Growth in the Arab Republic of Egypt - Mohieldin, Mahmoud; Hussein, Khaled; Rostom, Ahmed (World Bank, Washington, DC, 2019)
This paper discusses the evolution of the Egyptian banking sector and the main trends in financial development in the Arab Republic of Egypt. The paper examines empirically the relationship between the development of the financial sector and economic growth in Egypt between 1980 and 2016. It draws comparisons based on critical financial indicators between Egypt and selected emerging markets and developing economies, using a new data set of financial development indexes released by the International Monetary Fund. Econometric time-series modeling of bivariate regressions for real growth per capita and measures of financial development, to assess the relationship between financial development and economic growth in Egypt, yields three specific findings. First; there is a strong association between real growth per capita and financial development measured. Second; access to and the efficiency of banking services are not associated with real per capita income. Third, the Financial Markets Access Index—which compiles data on market capitalization outside the top 10 largest companies and the number of corporate issuers of debt—indicates that there is a robust association with real per capita gross domestic product. The main policy implications suggest that there should be a stronger focus on promoting a more proactive role for the financial services industry in Egypt. There is an especially critical role for bank financing to support the private sector to maintain an inclusive growth momentum. Further development of the capital market will promote the sustainability of such economic growth.